A novel approach to capillary plasma microsampling for quantitative bioanalysis. (May 2013) - Bowen, Chester L; Licea-Perez, Hermes; Karlinsey, Molly Z; Jurusik, Kristen; Pierre, Esaie; Siple, Joseph; Kenney, Jim; Stokes, Alan; Spooner, Neil; Evans, Christopher A
Background: A novel device and procedure for the collection and isolation of microvolumes of plasma have been developed and two pilot rodent PK studies have been completed.Results: This method involves collection of blood into a plastic-wrapped, EDTA-coated capillary tube, containing a small amount of a thixotropic gel and a porous plug. Following blood collection, the capillary is placed into a secondary labeled container suitable for centrifugation and plasma is generated. During centrifugation, the thixotropic gel isolates the plasma from the red blood cells and creates a physical barrier between the two matrices. The plasma is then dispensed from the capillary tube into a separate container for storage or processing.Conclusion: A simple and robust novel approach for the collection of small plasma volumes from rodent TK studies has been demonstrated.